2021
DOI: 10.21149/12300
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19, impacto psicosocial en estudiantes de medicina

Abstract: No disponible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…En este estudio la diferencia según la carrera estudiada no fue estadísticamente significativa, pero se encontró que los estudiantes de ciencias de la salud son los que generalmente se reconocen como una población de riesgo para padecer ansiedad y depresión en todo el mundo, esto se demostró en diferentes estudios (Garcia-Espinosa et al, 2021). En un estudio realizado en China el 25% presentaron ansiedad relacionada a la pandemia, siendo el principal factor el miedo al retraso en educación y el factor económico (Cao et al, 2020).…”
Section: Discussionunclassified
“…En este estudio la diferencia según la carrera estudiada no fue estadísticamente significativa, pero se encontró que los estudiantes de ciencias de la salud son los que generalmente se reconocen como una población de riesgo para padecer ansiedad y depresión en todo el mundo, esto se demostró en diferentes estudios (Garcia-Espinosa et al, 2021). En un estudio realizado en China el 25% presentaron ansiedad relacionada a la pandemia, siendo el principal factor el miedo al retraso en educación y el factor económico (Cao et al, 2020).…”
Section: Discussionunclassified
“…At Changzhi University, out of 7143 medical students, 24.9% had anxiety due to the pandemic (Garcia-Espinosa, Ortiz-Jiménez, Botello-Hernández, Hernández-Díaz, Góngor-Rivera, & Gecen, 2021). Garcia-Espinosa, et al (2021), also reported that, out of 530 medical students in Saudi Arabia, 38.11% reported being emotionally tired and 56.22% acknowledged a decrease in their academic ability during this pandemic. Finally, they state that the predisposing factors: being female, knowing someone with symptomatology and being a non-clinical semester student, generated moderate-severe anxiety in 61.3% of 348 medical students.…”
Section: Introductionmentioning
confidence: 97%